Teaching the whole teen everyday practices that promote success and resilience in school and life - Poliner, Rachel A.; Benson, Jeffrey (Thousand Oaks, California Corwin, 2017)
How can you help teens thrive now and for life? Support them as whole learners. Developing independence and responsibility. Collaborating and communicating effectively. Establishing valuable work habits. Harnessing emotions and motivation. In this insightful, culturally responsive guide, Poliner and Benson integrate these lifelong skills into daily practices through: Practical applications for diverse populations in every class, advisory, team, or club; The latest research on best practices from adolescent psychology, neuroscience, school climate; Tools for teachers, administrators, counselors, and parents to help teens succeed now and later in school, home, workplace, and community. Teaching the Whole Teen supports adolescents and adults within the school to thrive. -- Provided by publisher.
Part I. Seeing the whole teen -- Chapter 1. The whole teen comes into the school -- Chapter 2. The whole teen comes into a dominant culture -- Part II. Everyday practices -- Chapter 3. Connecting to adults and peers, not just to academics -- Chapter 4. Creating a culture of shared responsibility, not just obeying -- Chapter 5. Learning collaboratively, not just nearby -- Chapter 6. Communicating effectively, not just mumbling, exploding, avoiding, or texting -- Chapter 7. Managing work and developing a work ethic, not just passing or cramming -- Chapter 8. Developing emotional skillfulness proactively, not just reactively -- Chapter 9. Becoming more independent, not just alone -- Chapter 10. Connecting lessons to life, not just to tests -- Part III. The whole school surrounds the whole teen -- Chapter 11. Leaders set the tone for themselves and others -- Chapter 12. Schoolwide structures, practices, and policies that support the whole teen -- Chapter 13. Faculty culture that supports the whole teen -- Chapter 14. The novice teacher comes into the school.
Includes bibliographical references (pages 255-259) and index.
Keywords: Teenagers -- Education; Teenagers -- Conduct of life; Adolescence; Holistic education